Redesign de livro de partituras - Nardino, Caroline (2011)
This study aims to investigate the specific needs of the users scores and try to solve these problems so that we can achieve a satisfactory result positive about the usability of the product. For this study, was first formulated and applied a questionnaire to musicians, in order to find out what were the main problems found in the scores. Subsequently, the results of the questionnaire was explained and added to the analysis made by the author. Then the real work has developed. Were created illustrations for the book and it was transformed into bilingual. After the material ready and finished, the end result was put to the test in front of music professionals so that they approve or not the needs observed during the work.